2020
DOI: 10.3389/fpsyg.2020.01389
|View full text |Cite
|
Sign up to set email alerts
|

Technical-Tactical Behaviors Analysis of Male and Female Judo Cadets’ Combats

Abstract: This brief research report showed technical-tactical behaviors of male and female judo cadets during combats, comparing the frequency and time of judo combat actions, techniques and penalties. The data was composed for 3,240 sequential technical-tactical behavior analysis from 108 female and 300 male cadet combats recorded of public judo championships. Combat, standing combat moments, approach action, gripping action, attack, groundwork actions and pause moment were observed and determinant technical-tactical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…Therefore, preparation indicators did not change, whereas shortening of the fight time caused the necessity of changing the physiological profile of the female players. The necessity to modify the method of endurance training caused by this fact could have influenced the profile of technical and tactical preparation [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, preparation indicators did not change, whereas shortening of the fight time caused the necessity of changing the physiological profile of the female players. The necessity to modify the method of endurance training caused by this fact could have influenced the profile of technical and tactical preparation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are many up-to-date developments that analyze judo bouts in terms of technical and tactical actions [10,[13][14][15][16]. Gutiérrez-Santiago et al [7] analyzed the fights during the World Championships in judo in 2017 in the 66-73 kg weight division.…”
Section: Introductionmentioning
confidence: 99%
“…Technical and tactical analyses are common methods used in modifying the process of sport training in a group of martial arts and combat sports coaches and competitors. Interesting articles on this topic can be found in judo [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the analysis of selected literature show that studies are concerned with success prognosis based on morpho-functional, physiological, biomechanical and psychosomatic indices [ 24 ], as well as assessment of capacity during fights [ 25 , 26 ]. Other studies were concerned with movement analysis [ 8 ], traumas and starting consequences [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, anxiety control and emotional intelligence are necessary not only on the day of competition but also in the preparation period, when athletes have to manage their weight and deal with a stressful training program (Merino Fernández et al, 2020). Previous studies have to some extent identified the variables that can be considered as KPIs for judo performance; these including weight management (Escobar-Molina et al, 2016;Thomson et al, 2017;Gallot et al, 2019), level of strength (Ache Dias et al, 2012;Franchini et al, 2019), technical and tactical skills (Weigelt et al, 2011;Bocioaca, 2014;Miarka et al, 2020), level and direction of motivation (Gillet et al, 2010;Boughattas et al, 2017;Oliveira et al, 2018), nutrition (Artioli et al, 2019), capacity for focus and attention (Yahija, 2010;Jacini et al, 2012;Mihailescu and Sava, 2013;Toh et al, 2018;Campos Faro et al, 2020), sleep habits (Chtourou et al, 2018;Knowles et al, 2018;Vlahoyiannis et al, in press), speed (Almansba et al, 2008), and level of conditioning capacity (aerobic and anaerobic; Detanico et al, 2012;Franchini et al, 2014Franchini et al, , 2016Hesari et al, 2014;Anthierens et al, 2016).…”
Section: Introductionmentioning
confidence: 99%